Determination of the celluloseand lipid-containing components influence on the extrudate technological indicators - Petik, Ihor; Litvinenko, Olena; Stankevych, Serhii; Zabrodina, Inna; Ponomarova, Maryna; Kotliar, Oleh; Kliuchko, Ruslan; Muhalenko, Oleksii; Pidpala, Tetiana; Danylchuk, Galyna (Технологічний центр, 2024)
The effect of cellulose- and lipid-containing components on the technological parameters of the extruded mixture based on protein- and starch-containing raw materials on the technological parameters of the extrudate was studied. The use of components that modify such technological indicators of the extruded mixture as water resistance and swelling is substantiated. It is proposed to use sunflower husks and sunflower phosphatide concentrate as modifying additives to the mixture for extrusion. A rational ratio of the specified components in the extrudate was established to obtain indicators of water resistance in the range of 220...300 min and swelling in the range of 100...120 %. This is an important aspect of expanding the range of extruded products from the waste of oil and fat industries and obtaining high-quality competitive products. The object of the study is the dependence of water resistance and swelling of the extruded mixture on the content of modifying additives. Their rational ratio in the extrudate is: sunflower husk – 6.0 %; sunflower phosphatide concentrate – 5.0 %. The manufactured extrudate sample corresponds to commercial fish feed in terms of chemical composition and technological parameters, and also has a 4 times lower cost. A feature of the obtained results is the possibility of regulating the water resistance, swelling and porosity of the extrudate based on proteinand starch-containing raw materials, depending on the ratio of cellulose- and lipid-containing modifying additives. This allows to change the technological parameters of the finished product depending on the chemical composition of the mixture of raw components according to the requirements of the consumer. The results of the conducted research prove that cellulose- and lipid-containing secondary products of production can be successfully transformed into new competitive products.
Keywords: vegetable extrudate; cellulose-containing components; lipid-containing components; sunflower husk; sunflower phosphatide concentrate